Two different fucosylated chondroitin sulfates: Structural elucidation, stimulating hematopoiesis and immune-enhancing effects. (15th February 2020) - Niu, Qingfeng; Li, Guoyun; Li, Chao; Li, Qinying; Li, Jia; Liu, Chanjuan; Pan, Lin; Li, Shijie; Cai, Chao; Hao, JieJie; Yu, Guangli
Highlights: The structures of two FCSs with different sulfated fucosyl branches were elucidated. Fucosylated branches with different degree of polymerization (1–4) were found in FCS hp and FCS ht . FCSs could stimulate hematopoiesis and improve cardiac function. The α-l -Fuc2, 4S branches were more important to the activity. Abstract: Two fucosylated chondroitin sulfates FCS hp and FCS ht were isolated from the sea cucumber Holothuria polii and Holothuria tubulosa, respectively. The NMR spectroscopy and HILIC-FTMS methods were applied for their detailed structural characterization. Chemical analysis indicated that the two FCSs all contained a chondroitin sulfate backbone chondroitin sulfate-like core and fucosyl branches of α-L-Fuc2, 4S, α-L-Fuc4S or α-L-Fuc3, 4S linked to O -3 of glucuronic acid residues. The main branches of FCS hp and FCS ht were monofucose, and the small amounts of di-, tri- and tetrafucose with α-1, 3-linkage type were also detected. Finally, we investigated the immunomodulatory function of FCS hp and FCS ht in cyclophosphamide (CTX)-induced immunosuppressed mouse models. The results showed that FCS hp and FCS ht had beneficial effects on hematopoietic function recovery in CTX-induced bone marrow suppression mice. Notably, the α-L-Fuc2, 4S was more important to the activity than α-L-Fuc3, 4S. These results provided basis for developing the drugs to reduce side effects of chemotherapy.